The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/10669817.2017.1343538
|View full text |Cite
|
Sign up to set email alerts
|

Pain pattern classification and directional preference are associated with clinical outcomes for patients with low back pain

Abstract: Pain Pattern Classification (PPC) and Directional Preference (DP) have shown merit as reliable and predictable clinical solutions to help reduce the burden posed by low back pain (LBP). We conducted a prospective, observational cohort study to verify the association between PPC, DP, and clinical outcomes. We hypothesized that (1) patients who demonstrated DP Centralization (CEN) would have lower pain intensity and disability at follow-up than patients who demonstrated Non-DP Non-CEN, and (2) the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…No studies aimed to assess the classification on pain intensity in a multivariate model when adjusted for baseline values. For disability, five studies showed no significant benefit of classification on prognosis 117,128,130,134,137 , while five showed a significant effect 114,120,124,138,139 . Only two studies assessed disability prognosis within multivariate models, with one showing significant 138 and one non-significant results 137 .…”
Section: Mckenzie Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…No studies aimed to assess the classification on pain intensity in a multivariate model when adjusted for baseline values. For disability, five studies showed no significant benefit of classification on prognosis 117,128,130,134,137 , while five showed a significant effect 114,120,124,138,139 . Only two studies assessed disability prognosis within multivariate models, with one showing significant 138 and one non-significant results 137 .…”
Section: Mckenzie Methodsmentioning
confidence: 92%
“…Four studies reported the follow-up as when the patient was discharged; however, they did not provide a timeframe 114,130,138,139 . Three studies showed that classification was a significant predictor of pain intensity in univariate models 114,135,139 , while one did not 117 . No studies aimed to assess the classification on pain intensity in a multivariate model when adjusted for baseline values.…”
Section: Mckenzie Methodsmentioning
confidence: 99%
“…Pain and stiffness are often considered the primary deficits targeted by manual therapy. The ability of patients to perceive and report changes in pain location and intensity occurring during treatment has been clearly demonstrated in the literature on centralisation (May, Runge and Aina, 2018;Yarznbowicz et al, 2018) The ability of clinicians to perceive differences in stiffness within a treatment session is less clearly established. There is evidence that differences in PA stiffness related to symptoms are greater than the approximately 10% differences needed to be palpable by manual palpation (Tuttle and Hazle, 2018).…”
Section: Relevant Differences Perceivablementioning
confidence: 99%
“…The first study was a prospective, observational cohort study examining the association between Pain Pattern Classification (PPC), DP, and clinical outcomes (i.e. pain intensity and selfreported disability) [10]. The current study is a subgroup of patients who exhibited DP at the first examination in the absence of CEN.…”
Section: Designmentioning
confidence: 99%
“…Many different clinical profiles exist relative to DP assessment and DP should not be viewed as a homogeneous entity [5][6][7], nor can it be presumed that all patients with LBP will respond in the same way [8]. DP in the absence of CEN is common [9][10][11]; George et al reported that 50% of patients exhibited a DP without CEN [9], and CEN has found to be as low as 19.6% at the first examination [10,11]. However, the manner in which DP has been recorded in many studies has been inconsistent which may be leading to inconclusive research findings.…”
Section: Introductionmentioning
confidence: 99%